Evaluation of vitamin D-deficiency effects on the incidence of uterine fibroids - Shafq Al-azzawi; Dhafir Masheta; Rawnaq Kadhim (Faculty of Pharmacy, Mahidol University, 2022)
Uterine fibroids are a very common benign tumor in women of reproductive age due to unknown aetiology. There is growing evidence that vitamin D deficiency has a potential role in developing uterine fibroids. This study aims to investigate the effect of vitamin D levels in patients with uterine fibroids in Hilla city (a sunny city). The study was conducted on 70 women diagnosed with uterine fibroids that visited private clinics and were referred to biochemical laboratories. Vitamin D levels were assessed in patients' sera, and questionnaire data on age, body mass index, symptoms and drugs used were analysed. In addition, information from their ultrasound scans of the fibroids, including the size and the number of fibroids, were also recorded. The results demonstrated that more than half of patients had vitamin D deficiency and 25% of them were with insufficient vitamin D levels. The age group, 41-45 year, showed the lowest values, whereas no significant differences in vitamin D levels were observed in body mass index and severity of symptoms parameters. The results also revealed that a significant decrease in vitamin D levels was associated with large size and multiple fibroids. It can be concluded that vitamin D has a great implication on the incidence of uterine fibroids, even in sunny cities.